2007
DOI: 10.1021/om7002738
|View full text |Cite
|
Sign up to set email alerts
|

Cerium(III) and Cerium(IV) Bis(η8-pentalene) Sandwich Complexes:  Synthetic, Structural, Spectroscopic, and Theoretical Studies

Abstract: The Ce(III) anionic bis(pentalene) sandwich complex K[Ce{C8H4(Si i Pr3-1,4)2}2] (1) has been prepared by treatment of CeCl3 with K2[C8H4(Si i Pr3-1,4)2] and crystallographically characterized as its 18-crown-6 complex. Oxidation of 1 with Ag[BPh4] affords the neutral, formally Ce(IV) sandwich complex [Ce{C8H4(Si i Pr3-1,4)2}2] (2), whose molecular structure has also been determined. The electronic structure of 2 has been investigated in detail by a combination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
43
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 52 publications
(85 reference statements)
12
43
0
Order By: Relevance
“…(5) In an attempt to prepare an authentic sample of (η 8 -atoms in 5 as the 'ate' complex shown Figure S3 of the ESI, however the low quality of the data precluded accurate refinement of metric parameters. There is precedent for such Ln(III) anionic bis(pentalene) sandwich complexes with Ln = Ce, 71,72 emphasising the steric and electronic stabilisation achieved for the f-elements with the pentalene ligand in η 8 -mode.…”
Section: Redox Reactionsmentioning
confidence: 99%
“…(5) In an attempt to prepare an authentic sample of (η 8 -atoms in 5 as the 'ate' complex shown Figure S3 of the ESI, however the low quality of the data precluded accurate refinement of metric parameters. There is precedent for such Ln(III) anionic bis(pentalene) sandwich complexes with Ln = Ce, 71,72 emphasising the steric and electronic stabilisation achieved for the f-elements with the pentalene ligand in η 8 -mode.…”
Section: Redox Reactionsmentioning
confidence: 99%
“…[19] Examples of organometallic Ce IV complexes are also rare. The synthesis of [CeA C H T U N G T R E N N U N G (cot) 2 ] [28] (cot = cyclooctatetraenyl) and related complexes, [29][30][31] combining a highly oxidising metal cation with a reducing anionic ligand, has led to intensive study and debate into assignment of the metal oxidation state. [32][33][34][35][36][37] The first Ce IV cyclopentadienyl complex [38] was the tris(cyclopentadienyl)-supported Ce IV isopropoxide (D) reported by Marks et al, [39] closely followed by the crystallographically characterised tert-butoxide analogue reported by Evans et al [40] We have demonstrated the synthesis of [CeL 4 ] (L= OCMe 2 CH 2 (CNCHCHNiPr); E).…”
Section: ] (Nn' = [N-mentioning
confidence: 99%
“…Recent experimental and theoretical studies of certain Ce-and Yb-based organometallic complexes [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] have highlighted the importance of multiconfigurational interactions in understanding their electronic, structural, and magnetic properties. The canonical examples include Ce(cot) 2 , also known as "cerocene," where cot = cyclooctatetraene = C 8 H 8 , and Cp * 2 Yb(bipy), where Cp * = pentamethylcyclopentadienyl, and bipy = 2,2 ′ -bipyridine.…”
Section: Introductionmentioning
confidence: 99%